Global Fluoroquinolone Resistance Epidemiology and Implictions for Clinical Use - Axel Dalhoff (Interdisciplinary Perspectives on Infectious Diseases)
This paper on the fluoroquinolone resistance epidemiology stratifies the data according to the different prescription patterns by either primary or tertiary caregivers and by indication. Global surveillance studies demonstrate that fluoroquinolone resistance rates increased in the past years in almost all bacterial species except S. pneumoniae and H. influenzae, causing community-acquired respiratory tract infections. However, 10 to 30% of these isolates harbored first-step mutations conferring low level fluoroquinolone resistance. Fluoroquinolone resistance increased in Enterobacteriaceae causing community acquired or healthcare associated urinary tract infections and intraabdominal infections, exceeding 50% in some parts of the world, particularly in Asia. One to two-thirds of Enterobacteriaceae producing extended spectrum -lactamases were fluoroquinolone resistant too. Furthermore, fluoroquinolones select for methicillin resistance in Staphylococci. Neisseria gonorrhoeae acquired fluoroquinolone resistance rapidly; actual resistance rates are highly variable and can be as high as almost 100%, particularly in Asia, whereas resistance rates in Europe and North America range from <10% in rural areas to >30% in established sexual networks. In general, the continued increase in fluoroquinolone resistance affects patient management and necessitates changes in some guidelines, for example, treatment of urinary tract, intra-abdominal, skin and skin structure infections, and traveller’s diarrhea, or even precludes the use in indications like sexually transmitted diseases and enteric fever.